2000
DOI: 10.1007/s002130000497
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine self-administration in rats: estrous cycle effects, sex differences and nicotinic receptor binding

Abstract: These results suggest that while males and females may regulate their intake of nicotine similarly under limited access conditions, the motivation to obtain nicotine is higher in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
251
8
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(296 citation statements)
references
References 88 publications
32
251
8
2
Order By: Relevance
“…Research by Donny et al, 2000 did not report sex differences in arterial or brain levels following IV nicotine administration in rats that previously self-administered IV nicotine (i.e., 0.02, 0.06, or 0.09 mg/kg/injection) according to fixed ratio (FR) and progressive ratio (PR) schedules of reinforcement. Although plasma and brain nicotine levels increased as a function of dose, no sex differences in arterial plasma or brain levels of nicotine were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Donny et al, 2000 did not report sex differences in arterial or brain levels following IV nicotine administration in rats that previously self-administered IV nicotine (i.e., 0.02, 0.06, or 0.09 mg/kg/injection) according to fixed ratio (FR) and progressive ratio (PR) schedules of reinforcement. Although plasma and brain nicotine levels increased as a function of dose, no sex differences in arterial plasma or brain levels of nicotine were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Sex is an important factor that mediates the neurobiological response to nicotine, and ultimately the course of dependence behavior in humans that abuse cigarettes. Basic science research has demonstrated nicotineinduced sex differences in rats by measuring various behavioral and non-behavioral indices (Rosecrans, 1971(Rosecrans, , 1972Battig, 1981;Grunberg et al, 1986;Levin et al, 1987;Kanyt et al, 1999;Booze, et al, 1999;Donny et al, 2000;Harrod et al, 2004;Chaudhri et al, 2005a), and epidemiological research strongly suggests sex differences in tobacco use and abuse (Waldron, 1991;Kandel et al, 1998;Westermeyer & Boedicker, 2000). Although there may be multiple factors which influence initiation and use of tobacco smoking, the neurobiological processes which mediate sex specific differences in response to nicotine are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding suggests that repeated response-dependent pairings between nicotine and a non-drug stimulus can enhance the reinforcing efficacy of the stimulus via Pavlovian conditioning, and subsequently increase its control over operant behavior. Removing the stimulus after animals have maintained responding for it during saline substitution causes a further decrease in lever pressing, providing additional support for this hypothesis (Cohen et al 2005;Caggiula et al 2001;Donny et al 2000). Finally, following extinction of responding induced by removing nicotine and concurrent non-drug stimuli, reinstatement of lever pressing can be stimulated by either priming infusions of nicotine (Chiamulera et al 1996;Shaham et al 1997;Andreoli et al 2003), or by presentations of a non-drug stimulus that was previously combined with nicotine (Caggiula et al 2001;Lesage et al 2004;Paterson et al 2005).…”
Section: Nonpharmacological Stimuli Contribute Significantly To Nicotmentioning
confidence: 94%
“…Second, the peak of the dose-response function in this condition is shifted to the right (0.06 mg/kg/inf; free base) relative to behavior reinforced by nicotine paired with a non-drug stimulus, where responding peaks at 0.02-0.03 mg/kg/inf (Corrigall and Coen 1989;Donny et al 2000;Donny et al 2003;Chaudhri et al 2005b). These data suggest that nicotine self-administration is less reliable in the absence of concurrent non-drug stimuli, and support the prior hypothesis that the primary reinforcing effects of nicotine alone are relatively weak.…”
Section: Nonpharmacological Stimuli Contribute Significantly To Nicotmentioning
confidence: 96%
See 1 more Smart Citation